Atrial septal stenting - How I do it? - Kothandam Sivakumar (Wolters Kluwer Medknow Publications, 2015)
A wide atrial communication is important to maintain hemodynamics in certain forms of congenital and acquired heart defects. In comparison to balloon septostomy or blade septostomy, atrial septal stenting provides a controlled, predictable, and long-lasting atrial communication. It often needs a prior Brockenbrough needle septal puncture to obtain a stable stent position. A stent deployed across a previously dilated and stretched oval foramen or tunnel form of oval foramen carries higher risk of embolization. This review provides technical tips to achieve a safe atrial septal stenting. Even though this is a "How to do it article," an initial discussion about the indications for atrial septal stenting is vital as the resultant size of the atrial septal communication should be tailored for each indication.